PENGARUH PUPUK CAIR HASIL FERMENTASI CACING TANAH (Lumbricus rubellus) TERHADAP PERTUMBUHAN VEGETATIF KEDELAI (Glycine max (L.) Merr.) - , RATNA SETIAWATI, Dr. Kumala Dewi, M.Sc., St. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Soybean (Glycine max L.) is one of important agricultural commodities. Unfortunately, the high demand of soybean cannot be fulfilled by local production. Various attempts have been done to increase soybean productivity, one of them is the utilization of fertilizers. The aim of this research was to evaluate the effects of fermented earthworm liquid fertilizer on vegetative growth of soybean (Glycine max L.). The experiment was arranged in a randomized complete block design (RCBD) with 2x6 factorial and seven replications for each combination treatment. The first factor was application methods of fertilizer: pouring the fertilizer on the soil (C1) and spraying the fertilizer to the leaves (C2). The second factor was fertilizer dosages: 0 ml/L (D0), 5 ml/L (D1), 10 ml/L (D2), 15 ml/L (D3), 20 ml/L (D4), and 25 ml/L (D5). Parameters observed were plant height, number and leaf area, number of root nodules, nitrate reductase activity, total chlorophyll content, dry weight, stomatal density, and length of epidermal stem cells. The results of this research showed that application of liquid fertilizer by pouring (C1) and spraying (C2) did not influence the number of leaves, nitrate reductase activity, and total chlorophyll content. C2 treatment increased the risk of leaf tissue damage. C1 treatment increased some parameters of vegetative growth, such as plant height, leaf area, number of root nodules, dry weight, stomatal density, and length of epidermal stem cells. Based on this research, the optimal treatment combination to increase the vegetative growth of soybean (Glycine max L.) is by pouring 25 ml/L fermented earthworm liquid fertilizer.